Low Prevalence of Inappropriate Shocks in Patients With Inherited Arrhythmia Syndromes With the Subcutaneous Implantable Defibrillator Single Center Experience and Long‐Term Follow‐Up. Issue 10 (17th October 2017) - Rudic, Boris; Tülümen, Erol; Berlin, Veronika; Röger, Susanne; Stach, Ksenija; Liebe, Volker; El‐Battrawy, Ibrahim; Dösch, Christina; Papavassiliu, Theano; Akin, Ibrahim; Borggrefe, Martin; Kuschyk, Jürgen
Abstract : Background: Up to 40% of patients with transvenous implantable cardioverter‐defibrillator (ICD) experience lead‐associated complications and may suffer from high complication rates when lead extraction is indicated. Subcutaneous ICD may represent a feasible alternative; however, the efficacy of the subcutaneous ICD in the detection and treatment of ventricular arrhythmias in patients with hereditary arrhythmia syndromes has not been fully evaluated. Methods and Results: Patients with primary hereditary arrhythmia syndromes who fulfilled indication for defibrillator placement were eligible for enrollment. Between 2010 and 2016, 62 consecutive patients with primary hereditary arrhythmia syndromes, without indication for antibradycardia therapy, were enrolled in the study. Mean follow‐up was 31.0±14.2 months. The study cohort comprised of 24 patients with Brugada syndrome, 17 with idiopathic ventricular fibrillation, 6 with long‐QT syndrome, 1 with short‐QT syndrome, 3 with catecholaminergic polymorphic ventricular tachycardia, 8 with hypertrophic cardiomyopathy, and 3 with arrhythmogenic right ventricular cardiomyopathy. Thirty‐nine patients were implanted for secondary prevention. Twenty‐two patients had a previous transvenous ICD implanted, but required revision because of infection or lead defects. A total of 20 spontaneous ventricular tachyarrhythmias requiring shock intervention occurred in 10 patients during follow‐up. All episodes were terminated within the first ICD shock delivery with 80 J. Two patients had inappropriate therapies caused by oversensing following an uneventful implantation. No pocket‐site infections and no premature revisions have occurred during follow‐up. Conclusions: Our study supports the use of the subcutaneous ICD for both secondary and primary prevention of sudden cardiac death as a reliable alternative to the conventional transvenous ICD.